Analysis of Service Quality on Customer Satisfaction of Bank Central Asia, tbk (Case Study of KCP Mall Kelapa Gading III) - Rochayati Febriarhamadini; Maidiana Krisnawati (MultiTech Publisher, 2023)
This research aims to determine the effect of Service Quality, which consists of service quality dimensions, on Customer Satisfaction at Bank Central Asia, Kelapa Gading III Mall Branch. This research is quantitative, the population of this research is customers of Bank Central Asia Kelapa Gading III Mall branch. The total sample was 121 respondents, while the sampling technique used a sampling technique. The data for this research is primary data sourced from questionnaires that have been tested for validity and reliability, the data of which is processed using SPSS 24 to determine the results of correlation, determination, linear equations, and partial and multiple regression in hypothesis testing, both partial and simultaneous. The results of this research show that: 1) Customer satisfaction is positively and significantly impacted by tangibles. 2) Customer satisfaction is positively and significantly impacted by reliability; 3) customer satisfaction is positively and significantly impacted by responsiveness; 4) customer satisfaction is positively and significantly impacted by assurance; 5) customer satisfaction is positively and significantly impacted by empathy; and 6) tangible, responsiveness, empathy, assurance, and reliability all positively and significantly impact customer satisfaction.